Organizational power and politics: The narcissist's advantage?. (November 2021) - O'Reilly, Charles A.; Pfeffer, Jeffrey
Abstract: Research has shown that grandiose narcissists often rise to positions of power in organizations, even though there is little evidence that they perform better. Indeed, some studies show various deleterious effects on both their companies and the people who work for them. Prior research suggests that one reason for narcissist's success is that they are more skilled at organizational politics. One plausible implication is that narcissists are more willing to use a broad range of power tactics, in part because research shows that narcissists are less prone to feeling guilt for their behaviors. Using a sample of fully-employed adults (n = 270), we show that narcissism is correlated with a greater willingness to use tougher, more aggressive political tactics, an effect that is stronger to the extent that people are less guilt prone. Because research shows the importance of political skill for career success, our findings help account for why narcissism may produce more favorable career outcomes.